2009
DOI: 10.1002/art.24734
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic factors predictive of mortality in early systemic sclerosis

Abstract: Objective. To investigate the clinical and genetic variables at initial presentation that predict survival in the Genetics versus Environment in Scleroderma Outcome Study (GENISOS) cohort. Methods. GENISOS is a prospective, observational study of a multiethnic early systemic sclerosis (SSc) cohort. To date, a total of 250 patients have been enrolled. In addition to clinical and laboratory data, electrocardiograms (EKGs), chest radiographs, and pulmonary function tests have been obtained from each patient. A mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 87 publications
3
79
0
1
Order By: Relevance
“…In our sample, the patients had a mean disease duration of 42 years, were predominantly female (92% of the sample) and the most prevalent form was the limited one -which affected 54% of all patients. The demographic pattern of the sample reflects a pattern that is typically found in this disease according to the literature 15,16 . The overlap form displayed higher levels of ET-1.…”
mentioning
confidence: 58%
“…In our sample, the patients had a mean disease duration of 42 years, were predominantly female (92% of the sample) and the most prevalent form was the limited one -which affected 54% of all patients. The demographic pattern of the sample reflects a pattern that is typically found in this disease according to the literature 15,16 . The overlap form displayed higher levels of ET-1.…”
mentioning
confidence: 58%
“…The DRB1*1104 was found to be increased in patients with ATA. An additional epidemiologic study in the GENISOS (Genetics Versus Environment in Scleroderma Outcome Study) cohort found that HLA-DRB1*0802 and DQA1*0501 allotypes were independent predictors of mortality in addition to other factors (eg, body mass index, age >65 years, forced vital capacity 50% lower than predicted, presence of arrhythmia on electrocardiogram, pulmonary fibrosis, and absence of ACA) [10].…”
Section: Hlamentioning
confidence: 99%
“…1 Systemic scleroderma is a heterogeneous disease ranging from a mild form characterized by lesser involvement of internal organs to a more severe type characterized by greater involvement of these organs and rapid progression, leading to disability and even death in some cases. 2 Systemic sclerosis affects women more than men, in proportions of 4:1. 3 The prevalence ranges from seven to 489 cases per million individuals.…”
Section: Introductionmentioning
confidence: 99%